Is the Phenylalanine-Restricted Diet a Risk Factor for Overweight or Obesity in Patients with Phenylketonuria (PKU)? A Systematic Review and Meta-Analysis - Rodrigues, Catarina (2022)
Funding: CINTESIS—UIDB/4255/2020 a program financially supported by Fundação para a Ciência e Tecnologia/Ministério da Educação e Ciência, through national funds is acknowledged. Support from Human Nutrition and Metabolism Master Program from NOVA Medical School, Universidade Nova de Lisboa is ackowledged.